Carotid Artery-Cavernous Segment Injury during an Endoscopic Endonasal Surgery: A Case Report and Literature Review of the Overlooked Option for Surgical Trapping in the Hyperacute Phase - Kahilogullari, Gokmen; Bahadır, Burak; Bozkurt, Melih; Akcalar, Seray; Balci, Sinan; Arat, Anil (Journal of Neurological Surgery Reports, 2021)
Internal carotid artery (ICA) injury is a catastrophic complication of endoscopic endonasal surgery (EES). However, its standard management, emergent endovascular treatment, may not always be available, and the transnasal approach may be insufficient to achieve hemostasis.A 44-year-old woman with pituitary adenoma underwent EES complicated with the ICA cavernous segment injury (CSI). In urgent intraoperative angiogram, a good collateral flow from the contralateral carotid circulation was observed. Due to the unavailability of intraoperative embolization, emergent surgical trapping was performed by combined transcranial and cervical approach. The patient recovered but later developed a giant cavernous pseudoaneurysm. During the pseudoaneurysm embolization, ICA was directly accessed via a 1.7-F puncture hole using a bare microcatheter technique. Then, both the aneurysm and parent artery were obliterated with coils. At the 4-year follow-up, the patient was asymptomatic without a residual tumor. To our knowledge, this is the first case of ICA–CSI during EES successfully treated with ICA trapping as a lifesaving urgent surgery that achieved a complete recovery after a pseudoaneurysm embolization. Although several studies reported that EES-related ICA–CSIs with percutaneous carotid artery access, neither our surgical salvage technique nor our carotid access and tract embolization techniques were previously described.
Keywords: endonasal endoscopic surgery; endovascular treatment; ICA-cavernous segment; pituitary adenoma; trapping; urgent transcranial surgery